Pengaruh Big Five Personality terhadap Skeptisisme Profesional Auditor - Laura Callista Wijaya; Charoline Cheisviyanny (Jurnal Eksplorasi Akuntansi, 2024)
This study aims to analyze the influence of the big five personality traits on auditors' professional skepticism. The big five personality traits include extraversion, agreeableness, conscientiousness, neuroticism, and openness to experience. This research employs an associative causality study with a quantitative approach. Primary data were collected using questionnaires, and the sample consists of auditors working in Public Accounting Firms in Padang and Pekanbaru, selected through total sampling. Hypotheses were tested using multiple linear regression analysis with SPSS 25. The results indicate that extraversion, conscientiousness, and openness to experience have a positive impact on auditors' professional skepticism, while neuroticism has a negative impact. However, agreeableness does not significantly affect professional skepticism. Future research may consider incorporating additional variables or expanding the population to gain broader insights.